Executive Director’s Message - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2014)
ORNAC’s members are its most valuable asset. As ambassadors in your work place, as advocates for perioperative registered nursing practice and patient safety, as mentors to the next generation of students, and as involved supporters members are integral to ORNAC and vital to its success.